Prevalence of eating disorders and picking-nibbling in elderly women - Conceição, Eva Martins (2017)
ObjectiveThe aim of this study was to examine the point prevalence of eating disorders and picking/nibbling in elderly women.MethodsThis was a two-stage epidemiological study that assessed 342 women aged 65-94 years old. In Stage 1, the following screening measures were used to identify possible cases: the Mini-Mental State Examination, to screen and exclude patients with cognitive impairment; Weight Concerns Scale; SCOFF (Sick, Control, One, Fat, Food) Questionnaire; Eating Disorder Examination Questionnairedietary restraint subscale; and three questions to screen for picking/nibbling and night eating syndrome. Women selected for Stage 2 (n=118) were interviewed using the diagnostic items of the Eating Disorder Examination.ResultsAccording to the DSM-5, the prevalence of all eating disorders was 3.25% (1.83-5.7, 95% C.I.). Prevalence of binge-eating disorder was 1.68% (0.82-3.82, 95% C.I.), of other specified feeding or eating disorders was 1.48% (0.63-3.42, 95% C.I.), and of bulimia nervosa 0.3% (.05-1.7, 95% C.I.)]. Binge-eating episodes were reported by 5.62% of women. No cases of anorexia nervosa or night eating syndrome were identified. The prevalence of picking/nibbling was 18.9%. Picking/nibbling was associated with increased body mass index (t(322)=-3.28, p<.001) and binge-eating episodes ((2)(1)=5.65, p<.017).DiscussionPrevalence rates of eating disorders on elderly Portuguese women were comparable to those found on young women. Our data support the literature that suggests that binge-eating disorder is particularly prevalent in older adults. Picking/nibbling was the most prevalent eating behavior and we provide further evidence for its association with weight and disordered eating.